(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Copper sulphate is widely used in agriculture and aquaculture to control pests and pathogens; however, its accumulation in aquatic environments raises concerns regarding its toxic effects on non-target organisms, particularly freshwater teleost fishes. This study aims to investigate the histopathological alterations induced by copper sulphate exposure in the reproductive organs of selected freshwater teleost species. Specimens were exposed to sublethal concentrations of copper sulphate over an extended period under controlled laboratory conditions. Detailed microscopic examinations of ovarian and testicular tissues were conducted to identify structural changes, including degeneration of germ cells, oocyte atresia, testicular necrosis, vacuolization, and disruption of normal tissue architecture. The results revealed dose- and time-dependent histological damages, suggesting that copper sulphate induces significant reproductive toxicity by impairing the integrity of gonadal tissues. These morphological alterations are indicative of impaired gametogenesis and reduced reproductive potential, which could have serious implications for fish population sustainability in contaminated habitats. This research underscores the need for stringent monitoring of copper levels in freshwater ecosystems and highlights histopathology as a valuable tool for assessing sublethal toxic effects on fish reproduction. The findings contribute to a better understanding of the ecological risks posed by copper sulphate pollution and support the development of environmentally safer management practices.